Vol 2 no 2 Tahun 2024 IMPLEMENTASI PENGGALIAN ZAKAT PROFESI: (STUDI PADA PAYROLL ZAKAT ASN KABUPATEN KENDAL) - Masruri, Masruri (PRODI ES SEKOLAH TINGGI ISLAM KENDAL, 2024)
BAZNAS Kendal Regency's efforts are to eksplore the acquisition of the zakat target of the Kendal National Amil Zakat Agency (Baznas) in 2019, targeting to collect zakat of Rp. 6,385,000,000,-. This target has increased by around 300 percent or three times the figure in 2018 which only reached IDR. 2,025,413,276,-. And after the payroll was realized, the collection of zakat experienced an extraordinary increase, in 2022, Baznas' exploration of accumulative zakat, infaq and sodaqah reached Rp. 10,109,426,273,- while in 2023 it will increase to Rp. 10,403,019,495,- This Payroll application is not free of access. Many polemics, problems and responses have arisen regarding the ASN's zakat obligation. Namely regarding the nature of coercion in payroll applications, the zakat nishob value of ASN salaries is also not necessarily achieved, and the reduced exploration of zakat institutions outside Baznas which had previously been chosen by ASN, such as Lazisnu, lazismu, etc., which also target the subject of ASN zakat . This article was prepared using a normative juridical library research approach, Normative Juridical Research. Normative Legal Research (normative juridical) is a legal research method carried out by examining mere library materials. This research activity also collects data from various literature. Where researchers do this by taking notes, reading, studying, reviewing, or analyzing the required materials.